ANALI ANALISIS TINGKAT PENJUALAN DAN PERSEDIAAN BARANG DAGANG TERHADAP LABA PERUSAHAAN PADA PT BALAM JAYA SENTOSA KOTA BATAM - Jurnal Akuntansi Barelang (JURNAL AKUNTANSI BARELANG, 2017)
This research aims to determine the anality of the level of sales and merchandise inventory of corporate profits PT. Balam Jaya Sentosa either partially or simultaneously. The study design used in this research is descriptive verification. Data collected by the data reports provided by the company and literature by researchers. The results showed that 1) the level of sales and a significant positive effect on corporate earnings partially. This can be seen from the analysis of the t test showed tscore> ttable (29.337> 2.014). Great influence sales level of corporate profits is 0.539. 2) inventory merchandise positive and significant impact on corporate earnings partially. This can be seen from the analysis of the t test showed tscore> ttable (4.520> 2.014). The influence of the merchandise inventory on corporate earnings is 0.002. 3) the level of sales and inventory merchandise positive and significant impact on corporate earnings simultaneous. It is seen from the results of the F test analysis which shows Fscore> Ftable (487.682> 3.204). The regression equation Y'= - 0.005 + 0,539X1 + 0,002X2 + 0.001 with great influence sales and inventory levels of merchandise on corporate earnings is 95.4%, while the remaining 4.6% is influenced by other factors not included in this study.